Nghiên cứu giảm nhiễu điện cho pin nhiệt - Thảo, Phạm Mạnh; Tú, Doãn Anh; Tuân, Lã Minh; Kỳ, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
This paper describes an effort to overcome the short-circuit (sometimes called “electric noise”) causing by lithium-calcium alloy formed in the thermal cell with calcium metal as anode. In the first method, calcium-containing compounds were created on the surface by immersing anode calcium in glacial acetic acid solution in acetone, followed by drying stage at different temperatures. Compounds containing Ca2+ such as calcium oxide, calcium hydroxide, calcium acetate and carbonate inhibit the formation of CaLi2 alloy at the anode surface in contact with the electrolyte so that significantly reduced short-circuit in the cell. In another method, lithium chromate was added in the KCl-LiCl eutectic mixture in the separator. In cells applied both of the methods there wasn’t any “electric noise” observed. Keywords: Thermal cell, calcium anode, lithium-calcium alloy, lithium chromate.